Cyber-terrorism under the nigerian law: a new form of threat or an old threat in a new skin? (2018)
Cyber-terrorism is a new phenomenon that has found expression in the current legal literature on terrorism. The concept of terrorism itself is enigmatic as there is no commonly agreed definition. However, what constitutes acts of terrorism seems to be agreed upon by writer and legal philosophers and have been clearly proscribed under the laws of most jurisdictions. The difficulty entrenched in having a common definition for terrorism also has its impact on defining "cyber-terrorism" which also does not have an agreed definition. Cyber-terrorism takes on another dimension compared with the tradition terrorism due to the fact that it can only be carried out in the cyberspace needing no physical involvement in the location where the target is. The question that disturbs the mind is whether the cyber-terrorism poses another form of threat different from that of traditional terrorism which may require a separate law to address. It was realized that cyber-terrorism poses new threats that the extant legal provisions on terrorism in Nigeria cannot adequately handle due to the technicalities involved.